Discovery of the second European Amalopis species: an integrative survey of the widespread Pedicia (Amalopis) occulta (Meigen, 1830) (Insecta, Diptera, Pediciidae) - Ujvárosi, Lujza; Bálint, Miklós (Zootaxa, 2012)
Integrative taxonomy enhances species discovery and facilitates species delimitation by combining DNA sequence data,morphology, and distributional and ecological information. In this paper we use complementary methods of morphologyand DNA barcoding to delineate species boundaries in a widespread European spring-dwelling crane-fly, Pedicia (Amalo-pis) occulta (Meigen). We describe a previously overlooked large cryptic dipteran as Pedicia (Amalopis) fusca n. sp. Wealso designate the lectotype of P. occulta of the basis of a comprehensive study of relevant type specimens. Morphologicaldifferences between the two species are delicate but detectable, and comprise mostly male genital structures. However,the sequence divergence of 13.1% reflects an ancient divergence, which plausibly pre-dates the Pleistocene. The EuropeanAmalopis species differ significantly from all the rest of Amalopis species with Far East distributions, but share a numberof similarities with a species identified from the Himalayas, India and described as Pedicia (Tricyphona) ericarum Alexander, 1966. We also discuss a possible close relationship between P. ericarum and the European Amalopis species.